Decoupling fossil trackways from trackmaker identity in locomotion studies - Krapovickas, Verónica (Ichnos-An International Journal For Plant and Animal Traces, 2024)
This paper presents a novel Trackway Evidence-Based Approach, focusing on the direct evidence provided by fossil trackways to infer postures, movements, and behaviors of extinct tetrapods. Traditional methods link fossilized footprints with specific skeletal reconstructions, yet this approach can introduce biases if the assumed trackmaker’s identity is incorrect. By decoupling trackways from trackmaker assumptions, we propose a framework for analyzing locomotion independently, using morphometric and dynamic parameters derived solely from trackways. Current analytical tools allow for estimation of key parameters like trunk length, hip height, body mass, and foot posture directly from trackway evidence. Supported by a collaborative research program, we are also testing experimental approaches to validate these parameters and deepen our understanding of trackway morphology. Additionally, simplified gait simulations provide an efficient means to explore extinct animal biomechanics without the extensive demands of full-body musculoskeletal modelling. This approach aims to refine hypotheses on evolutionary trends in locomotion and posture, offering a valuable new perspective for paleobiologic reconstructions.
CRIS-Team Scopus Importer:2024-12-06
Keywords: evolutionary biomechanics; Fossil trackways; Gait simulation; morphometric analysis; neoichnology; tetrapod locomotion